Clinical impact of inflammation in dry eye disease: proceedings of the ODISSEY group meeting. Issue 2 (8th April 2017) - Baudouin, Christophe; Irkeç, Murat; Messmer, Elisabeth M.; Benítez‐del‐Castillo, José M.; Bonini, Stefano; Figueiredo, Francisco C.; Geerling, Gerd; Labetoulle, Marc; Lemp, Michael; Rolando, Maurizio; Van Setten, Gysbert; Aragona, Pasquale; et al.
Abstract: Dry eye disease (DED) is a common, multifactorial ocular condition with major impact on vision and quality of life. It is now well recognized that the pathophysiology of chronic DED can include a cycle of inflammation involving both innate and adaptive immune responses. Recently, in vitro/in vivo models have been used to obtain a better understanding of DED‐related inflammatory processes at molecular/cellular levels although they do not truly reproduce the complex and chronic hallmarks of human DED. In clinical DED research, advanced techniques such as impression cytology, conjunctival biopsy, in vivo confocal microscopy and multiplex tear analyses have allowed an improved assessment of inflammation in DED patients. This was supported by the identification of reliable inflammatory markers including matrix metalloproteinase‐9, human leucocyte antigen‐DR or intercellular adhesion molecule‐1 in tears and impression cytology samples. One of the current therapeutic strategies focuses on breaking the inflammatory cycle perpetuating the ocular surface disease, and preclinical/clinical research has led to the development of promising anti‐inflammatory compounds. For instance, cyclosporine, already approved in the United States, has recently been authorized in Europe to treat DED associated with severe keratitis. In addition, other agents such as corticosteroids, doxycycline and essential fatty acids, through their anti‐inflammatory properties, show encouraging results. We now have a clearer understanding of the inflammatory processes involved in DED, and there is hope that the still emerging preclinical/clinical findings will be translated into new and highly effective therapies for patients in the near future.